Ag2 and Ag3 Clusters: Synthesis, Characterization, and Interaction with DNA1. (12th May 2015) - Buceta, David; Busto, Natalia; Barone, Giampaolo; Leal, José M.; Domínguez, Fernando; Giovanetti, Lisandro J.; Requejo, Félix G.; García, Begoña; López‐Quintela, M. Arturo
Abstract Subnanometric samples, containing exclusively Ag2 and Ag3 clusters, were synthesized for the first time by kinetic control using an electrochemical technique without the use of surfactants or capping agents. By combination of thermodynamic and kinetic measurements and theoretical calculations, we show herein that Ag3 clusters interact with DNA through intercalation, inducing significant structural distortion to the DNA. The lifetime of Ag3 clusters in the intercalated position is two to three orders of magnitude longer than for classical organic intercalators, such as ethidium bromide or proflavine.